Four vertex technique for correcting urethral prolapse: technique description and cohort study - Noya-Mourullo, Andrea; Herrero-Polo, Manuel; Heredero-Zorzo, Oscar; García-Gómez, Francisco; Urrea-Serna, Carmen; Marquez-Sanchez, Magaly-Teresa; Flores-Fraile, Javier; Padilla-Fernandez, Barbara-Yolanda; Lorenzo-Gómez, María-Fernanda (Frontiers in Surgery, 2023)
Introduction/Objectives This study aims to describe the procedure and effectiveness of the four-vertex technique for correcting urethral prolapse in women. Methods and Materials includes a retrospective case series of 17 patients who underwent surgery for urethral prolapse. Two study groups were distinguished based on the presence or absence of pelvic heaviness symptoms. The variables were analyzed, including age, BMI, concomitant diseases, obstetric and gynecological history, time from diagnosis to surgery, and outcomes of treatment. Results All patients were postmenopausal, with a mean age at the time of the intervention of 70.41 years, with no differences between groups. Mean BMI was 23.67 kg/m2, higher in the group with a sensation of vaginal heaviness (p = 0.027). Mean time elapsed between diagnosis and operation was 231.58 days, with no differences between groups. Mean childbirth count was 2.29. The most frequent causes for consultation were urethrorrhagia (33.33%) and a bulging sensation (33.33%). After the intervention, 14 patients (82.35%) were asymptomatic, two (11.76%) had dysuria, and one (5.88%) had urinary urgency. Ten patients had pre-surgical urinary incontinence, which was resolved in nine patients. 17.46% subsequently presented pelvic organ prolapse. In three women there was secondary impairment of sexual activity. Conclusion The four-vertex technique was effective in resolving symptoms in most patients. However, some patients experienced dysuria, urinary urgency, and pelvic organ prolapse after surgery. Urinary incontinence improved in most patients, but a few required additional treatments with suburethral tape. The study also identified associations between variables and the presence of cystocele, consultation for a bulging sensation, and bleeding from urethral prolapse. Overall, this study sheds light on the challenges and outcomes of surgical treatment for urethral prolapse and provides valuable insights for future research in this area.